Lived experiences of prostituted males - Villaluz, Raul Paule (College of Education, University of the Philippines Diliman, 2018)
The study sought to examine the lived experiences and coping mechanisms of the prostituted males. A qualitative-phenomenological research design was employed to explore and gather a rich description of the phenomenon being undertaken. Eleven (11) prostituted males were purposely selected and have undergone a series of counseling interviews. Results showed that the lived experiences of prostituted males comprised of the following themes namely, (1) providing money for the family, (2) happenstance and positive consequences, and (3) becoming independent. Their lived experiences also revealed their motivations in continuing to engage in sex work. Family is the primary motivation of prostituted males in embarking on sex trade. Coping mechanisms evident to those participants are "shifting one's paradigm", reminding practically", and educating oneself". In addition, reality therapy is seen to be a helpful counseling paradigm for assisting prostituted males towards their well-being. Finally, implications to counseling practice, education, career development and mental health are discussed.